2003
DOI: 10.1007/s11661-003-0187-9
|View full text |Cite
|
Sign up to set email alerts
|

Toughness and strength characteristics of Nb-W-Si ternary alloys prepared by Arc melting

Abstract: This article describes the room-temperature and high-temperature mechanical properties and failure modes of series Nb-W-Si alloys-Nb-10W, Nb-10Si, Nb-10Si-5W, Nb-10W-5Si, and Nb-10W-10Si-prepared by arc melting. For the Nb-10W alloy, the microstructure was a monolithic Nb solid solution (Nb ss ) with a grain size up to a few hundred microns, while the other four alloys consisted of primary Nb ss and a eutectic of Nb ss /Nb 5 Si 3 (5-3 silicide) as a result of replacing Nb with Si. Among all alloys, the Nb-10W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 27 publications
(74 reference statements)
2
18
2
Order By: Relevance
“…The solid solution hardening on Ir supplied by Si is attributed to the structure and the atomic size differences between Ir and Si, subsequently, probably resulting in strong interaction between electrons of Ir and Si, elastic interaction for edge dislocations and increase of the stacking fault energy of the Ir solid solution [30,31]. A similar result has also been reported in the Nb-Si binary [25], in which the Nb solid solution obtained a 200 improvement in the HV by lesser than 1 mol% Si solute. The rate of solid solution hardening DHV of Si to Ir, defined as increasing of the HV by per 1 mol% solute, is 166 MPa/mol, while that for Nb to Ir with a size misfit parameter 5.3% is about 40 MPa/mol.…”
Section: Potential Of the Ir-si Alloy As A High-temperature Materialssupporting
confidence: 67%
See 1 more Smart Citation
“…The solid solution hardening on Ir supplied by Si is attributed to the structure and the atomic size differences between Ir and Si, subsequently, probably resulting in strong interaction between electrons of Ir and Si, elastic interaction for edge dislocations and increase of the stacking fault energy of the Ir solid solution [30,31]. A similar result has also been reported in the Nb-Si binary [25], in which the Nb solid solution obtained a 200 improvement in the HV by lesser than 1 mol% Si solute. The rate of solid solution hardening DHV of Si to Ir, defined as increasing of the HV by per 1 mol% solute, is 166 MPa/mol, while that for Nb to Ir with a size misfit parameter 5.3% is about 40 MPa/mol.…”
Section: Potential Of the Ir-si Alloy As A High-temperature Materialssupporting
confidence: 67%
“…An idea that introduces the solute Si into Ir or forms an fcc/silicide two-phase structure in Ir-based alloys is an interesting try. It is expected that a further improvement in the high temperature strength of the Ir-based alloys could be achieved by solid solution hardening on Ir by Si or the enhancing phase Ir/Si silicides, which had been proved to be a successful approach for supplying high temperature strength in Nb-Si based in situ composites [20][21][22][23][24][25][26]. Due to there is no continuous Ir-Si binary phase diagram below 50 mol% Si, basic phase and microstruatural evolution of Ir-Si binary alloys should be understood before design of the Ir-based alloys having Si dropped.…”
Section: Introductionmentioning
confidence: 99%
“…The refractory Nb-Si-based alloys with high melting temperatures are of interest as candidate materials for aero-engine applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The microstructure of the Nb-Si-based alloys consists of hard and brittle intermetallic Nb 5 Si 3 and relatively ductile Nb-solid solution (Nb ss ) phases. The Nb 5 Si 3 exhibits excellent high-temperature strength retention and creep resistance, [1] but poor ductility and fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…pct). It was reported that the Hv of the pure Nb was of about 82, [24] so the increment of the Hv from 82 of pure Nb to 331 of the Nb SS phase comes from the solute concentrations of 0.88Si + 22.94Ti + 5.33Hf + 6.71Cr (see compositions of the Nb SS phase in the 6Cr alloy in Table I). Another increment in the Hv of the Nb SS phase from 331 up to 377 is basically attributive to an increase of the Cr concentration in the Nb SS phase from 6.71 at.…”
Section: Discussionmentioning
confidence: 99%